1995
DOI: 10.1055/s-2006-958002
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Non-Protein Amino Acids in Seeds of the Guam Cycad,Cycas circinalis, by an Improved GC-MS Method

Abstract: The non-protein amino acid, beta-N-methyl-amino-L-alanine (L-BMAA) from Cycas circinalis seeds, has been implicated as a causative agent of amyotrophic lateral sclerosis-Parkinsonism dementia complex (ALS-PDC), a disease known from Guam and other areas in the western Pacific. We analyzed C. circinalis seeds for additional free non-protein amino acids by a recently developed GC-MS method. The samples were prepared by water extraction of seed flour. The amino acids present in the extract were derivatized by N(O,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Probable explanations for this finding include the possibilities that (i) Glu uptake and͞or distribution is limited in the antiAtGLR1.1 plants, or (ii) Glu is not the natural ligand and perhaps a BMAA-like molecule is the endogenous AtGLR1.1 ligand. The latter explanation is credible because BMAA is a plant-derived compound, found mainly in the cicads (28). Results from another laboratory demonstrated that the effects of an iGLR agonist are reversed only with high concentrations (10 mM) of Glu (8).…”
Section: Atglr11 Regulates the Accumulation Of Transcripts Involved mentioning
confidence: 96%
“…Probable explanations for this finding include the possibilities that (i) Glu uptake and͞or distribution is limited in the antiAtGLR1.1 plants, or (ii) Glu is not the natural ligand and perhaps a BMAA-like molecule is the endogenous AtGLR1.1 ligand. The latter explanation is credible because BMAA is a plant-derived compound, found mainly in the cicads (28). Results from another laboratory demonstrated that the effects of an iGLR agonist are reversed only with high concentrations (10 mM) of Glu (8).…”
Section: Atglr11 Regulates the Accumulation Of Transcripts Involved mentioning
confidence: 96%
“…Various amino acids able to activate subclasses of the ionotropic glutamate receptor family are also present, including b-N-oxalylamino-Lalanine (BOAA) and b-N-methylamino-L-alanine (BMAA), agonists for AMPA and NMDA receptors, respectively. A number of other compounds have also been detected in cycad, some still not well characterized [30,31]. Investigators in the 1960s seized on the toxicity of MAM, using either cycad or the isolated toxin in a series of experiments designed to demonstrate both the neuronal effects as well as the mechanisms of action.…”
Section: Is There a Neurological Rosetta Stone?mentioning
confidence: 99%
“…Analytical methods to detect the presence of BMAA in plant and animal tissue in the subpicomole range include gas chromatography mass spectrometry (GC/MS) 17 and reversed phase HPLC method with precolumn derivatization by 9 -fl uorenylmethyl chloroformate. 26 Based on an electrophysiology study of 29 Chamorro patients with neurodegenerative diseases, a peripheral neuropathy can occur in these patients.…”
Section: Diagnostic Testingmentioning
confidence: 99%